1987
DOI: 10.1111/j.1432-1033.1987.tb13323.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of alcohol/polyol dehydrogenases

Abstract: Sixteen characterized alcohol dehydrogenases and one sorbitol dehydrogenase have been aligned. The proteins represent two formally different enzyme activities (EC 1.1.1.1 and EC 1.1.1.14), three different types of molecule (dimeric alcohol dehydrogenase, tetrameric alcohol dehydrogenase, tetrameric sorbitol dehydrogenase), metalloproteins with different zinc contents (1 or 2 atoms per subunit), and polypeptide chains from different kingdoms and orders (mammals, higher plants, fungus, yeasts). Present compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
175
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(184 citation statements)
references
References 49 publications
8
175
1
Order By: Relevance
“…The deduced C. neoformans MPD sequence also contained the conserved Cys residues at positions 55 and 136 and the conserved His residue at position 78, which together form the active site for the zinc ligand. The deduced MPD sequence also contained Cys residues at positions 110, 113, 116 and 124, which are similar to the conserved Cys residues in the second zinc-binding site in yeast alcohol dehydrogenase (Jornvall et al, 1987). Comparison of C. neoformans MPD with other alcohol dehydrogenases also revealed a tetrameric quaternary structure similar to yeast alcohol dehydrogenases, which agrees with the experimental data.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The deduced C. neoformans MPD sequence also contained the conserved Cys residues at positions 55 and 136 and the conserved His residue at position 78, which together form the active site for the zinc ligand. The deduced MPD sequence also contained Cys residues at positions 110, 113, 116 and 124, which are similar to the conserved Cys residues in the second zinc-binding site in yeast alcohol dehydrogenase (Jornvall et al, 1987). Comparison of C. neoformans MPD with other alcohol dehydrogenases also revealed a tetrameric quaternary structure similar to yeast alcohol dehydrogenases, which agrees with the experimental data.…”
Section: Discussionsupporting
confidence: 80%
“…However, a  search of the GenBank and SWISS-PROT databases (Altschul et al, 1997) revealed that the deduced peptide was 43-47 % identical to long-chain alcohol\ polyol dehydrogenases from several fungi and that it was most similar to alcohol dehydrogenase III from Aspergillus nidulans. The deduced peptide also contained conserved residues for cofactor binding (Wierenga & Hol, 1983) and conserved residues for two active sites containing zinc (Jornvall et al, 1987) (Fig. 3).…”
Section: Cloning and Analysis Of The Mpd Cdnamentioning
confidence: 99%
“…Shortly thereafter, S. cerevisiae ADH4 [78] and E. coli propanediol oxidoreductase [6] were noted to share a significant degree of amino acid identity with Z. mobilis ADH2. Although this new type of ADH lacked homology with any other previously known ADHs [29], they were demonstrated to utilize ethanol, as well as number of other alcohols, as substrate(s) [6]. In the intervening years, a number of additional microbial enzymes of this iron-activated enzyme type have been described [11,32,50,54,73,83].…”
Section: Introductionmentioning
confidence: 94%
“…ADHFE1 also lacks the second of the three conserved histidine residues at the iron-binding region [12]. For the microbial ironactivated ADHs it is these three histidine residues that are thought to be involved in metal binding [29]. These features indicate that human ADHFE1 and its homologs in other species, despite their similarity to iron-activated microbial ADHs, may be of a unique nature in regard to possible enzymatic activities, catalytic mechanism, expression pattern, and function.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with other ADHs allowed classification of this enzyme into the zinc-containing, medium-chain alcohol/polyol dehydrogenase family which had been primarily described in eukaryotes [5]. Currently, this family is composed of the tetrameric and the dimeric subfamilies which in turn is divided into classes I±VI, C and P [6,7].…”
mentioning
confidence: 99%